Behavioral integration in the boardroom. Issue 3 (19th March 2021) - Pastra, Aspasia; Koufopoulos, Dimitrios N.; Samac, Nikola; Johansson, Tafsir
Abstract : Purpose: This study aims to understand the relationship between behavioral integration in the boardroom and board performance. Design/methodology/approach: The authors performed a series of multiple hierarchical regression analyses to explore research questions. Primary data were collected via questionnaires from 184 Nordic members to identify perceptions of behavioral integration and board performance in their boardroom. Findings: The authors found that different dimensions of behavioral integration have a different effect on board performance. The collaborative behavior of the board did not predict any dimension of board performance, whereas information exchange predicted one dimension of board performance, that of providing strategic leadership. The paramount role of joint decision-making is underlined in this study as this positively predicted all of the dimensions of board performance (strategic leadership, networking and readiness of the board). Research limitations/implications: Future research should investigate behavioral integration among board members using a longitudinal design and expand the sample cross-culturally. Practical implications: For forming high-performing teams, emphasis should be given on the joint decision-making. Understanding the joint problems, transparency in actions and discussion about the problem under consideration are of paramount importance for the effectiveness of the team. Social implications: Team's conversational environment has crucial impact on team outcomes. Originality/value: This is one of the rare studies that examine perceptions of executives about the level of behavioral integration in their board.